2019
DOI: 10.4102/ajod.v8i0.528
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of parents of children living with disabilities at Lehlaba Protective Workshop in Sekhukhune district of Limpopo province

Abstract: Background: Parents of children with disabilities have faced difficulties in looking after their children, be it socially, economically and financially. Parents in rural areas are mainly left with a huge burden, as there is a lack of services and support from both the state and non-governmental organisations. Parents in Sekhukhune district, a rural area in Limpopo province of South Africa, face challenges in raising their disabled children related to lack of resources and lack of services at their disposal.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…This is a network of families who will connect with, educate, and conduct outreach with others who have similar experiences, as well as link them to important services, resources, and information. The organisation hopes this initiative will help to address and decrease the physical, emotional, and experiential isolation many parents of children with disabilities feel [ 19 , 66 , 67 ]. Focusing all its energy and attention on direct service provision can limit an organisation’s scale and sustainability.…”
Section: A South African Example: the Shonaquip Social Enterprisementioning
confidence: 99%
See 1 more Smart Citation
“…This is a network of families who will connect with, educate, and conduct outreach with others who have similar experiences, as well as link them to important services, resources, and information. The organisation hopes this initiative will help to address and decrease the physical, emotional, and experiential isolation many parents of children with disabilities feel [ 19 , 66 , 67 ]. Focusing all its energy and attention on direct service provision can limit an organisation’s scale and sustainability.…”
Section: A South African Example: the Shonaquip Social Enterprisementioning
confidence: 99%
“…There is also a lack of synergy between different government departments and their agendas, despite the fact that disability can only be addressed intersectorally. Many ideological commitments to people with disabilities have not yet been translated into law or practicable guidelines [ 17 , 19 ]. For example, although government’s commitments to disabled people were reaffirmed in the 2016 White Paper on the Rights of People with Disabilities [ 20 ], by 2020 the Department of Social Development had not yet promulgated any disability-specific legislation in line with the White Paper [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Speculation about the child's disability amongst community members could possibly result from the lack of proper information on what causes a disability (Gona et al 2011;Taderera & Hall 2017). As previous studies in Kilifi and Limpompo have found that disability is associated with evil spirits, punishment from God or witchcraft, this could possibly explain the aspect of people spreading rumours (Gona et al 2011;Tigere & Makhubele 2019).…”
Section: Introductionmentioning
confidence: 98%
“…The diagnosis of disability in a child presents challenges for many parents and families (Huang, Kellett & St John 2010 ; Tigere & Makhubele 2019 ; Yaacob et al 2021 ). For most parents on learning about their children’s disability, shock becomes the first response to dealing with the diagnosis (Hemming & Akhurst 2009 ; Yaacob et al 2021 ), followed by refusal to accept the diagnosis, anger and fear of the unknown world that still needs to be travelled (Huang et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation